HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA DAN DUKUNGAN TENAGA KESEHATAN DENGAN KEPATUHAN MINUM OBAT PADA PENDERITA HIPERTENSI DI PUSKESMAS KECAMATAN PASAR REBO - Julia Totong; Albert Sanders; Annabela Takaliwang (Journal of Innovation Research and Knowledge, 2026)
Hypertension, a silent killer, remains a major challenge in Indonesia, with many cases still found in primary healthcare facilities. Hypertension patients require long-term therapy, and adherence is a crucial factor in determining the success of therapy. Hypertension is a chronic disease that requires patient adherence to medication. Patient adherence is influenced by various factors, including patient knowledge, family support, and access to health information. According to data from the Indonesian Ministry of Health (2023), 55.86% of hypertensive patients on the island of Java are non-compliant or do not regularly take their medication. Many factors influence medication adherence, such as knowledge level, age, gender, employment status, and duration of illness. The purpose of this study was to determine the effect of patient knowledge, family support, and access to health information on adherence among hypertensive patients at Pasar Rebo District Community Health Center, Jakarta.The success of hypertension therapy is greatly influenced by patient compliance in taking antihypertensive medication as recommended by healthcare professionals. Low compliance can lead to uncontrolled blood pressure and increase the risk of complications such as stroke, heart disease, and kidney failure. This study is a quantitative descriptive study with a cross-sectional method and used a questionnaire for data collection. The compliance level questionnaire used the MMAS-8. This study aims to analyze the relationship between knowledge, family support, and access to health information with compliance of hypertension patients at Pasar Rebo District Community Health Center, Jakarta. The study sample was hypertension patients selected using a purposive sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was performed using the chi-square test and logistic regression to determine the relationship between variables. The results showed that there was a significant relationship between knowledge, family support, and access to health information with adherence in hypertensive patients (p < 0.05). The most dominant variable influencing adherence was family support. The inclusion criteria of the study included outpatient hypertensive patients aged ≤ 65 years and currently receiving antihypertensive therapy. Data analysis was performed using the chi-square test and logistic regression to determine the relationship between variables. The results showed that there was a significant relationship between knowledge, family support, and access to health information with adherence in hypertensive patients (p < 0.05). The most dominant variable influencing adherence was family support. The results showed that 70 respondents met the criteria that could be used as research data. The results of the study based on age with a high level of compliance at the age of 18-40 years with 16 respondents (22.9%), while at the age of 41-60 years 8 respondents (11.4%), low at the age of> 60 years as many as 12 respondents (17.19%) and the results of P value = 0.044 <α = 0.05 are declared valid; Based on gender with patient compliance taking medication, high in men 21 respondents (30%), low in women (14.3%) P value = 0.041 <α = 0.005 is declared valid; The relationship between education with a high level of compliance taking medication is found in high school education with 11 respondents (15.7%) and low in college education (4.3%) and P value = 0.20 <α = 0.5 is declared valid; The relationship between work and compliance taking medication is high at the level of work as self-employed 15 respondents (21.4%). Meanwhile, for those who did not work with 9 respondents (12.9%), and low in civil servants with 5 respondents (7.1%), P value = 0.035 < α = 0.05 was declared valid, the relationship between the level of knowledge and compliance was said to be good for 20 respondents (26.6%), sufficient for 9 respondents (12.9%) and less for 2 respondents (31.4%) P value = 0.00 <0.05 was declared valid.